A cost-benefit analysis of sensor quality and spatial density for rapid regional post-event seismic damage assessment: Application to Istanbul. Issue 163 (December 2022) - Cheng, Qingle; Liao, Wenjie; Fei, Yifan; Tian, Yuan; Lu, Xinzheng; Zhang, Wenyang; Ghahari, Farid; Kurtulus, Asli; Taciroglu, Ertugrul
Abstract: A quantitative evaluation of the influence of sensor quality and spatial density on the results of rapid regional seismic damage evaluations of buildings can provide an important reference for the deployment of a strong-motion network. However, the influence of sensor quality and spatial density on seismic damage assessment is still unclear. Therefore, a cost-benefit analysis framework of sensor quality and spatial density for rapid regional post-event seismic damage assessment is proposed. In this framework, a simulation method for sensor-recorded ground motions and an interpolation-based ground motion field refinement method are used to consider the influence of the quality and density of the sensor network. The accuracies of seismic damage assessments with different sensor layout schemes were compared using the time-history analysis-based regional seismic damage assessment method, through which the influence of sensor quality and spatial density on the seismic damage assessment can be quantitatively evaluated. Finally, the Zeytinburnu district of Istanbul was selected as an example for illustrating the proposed framework. The main conclusions are as follows: (1) the spatial density of the sensors used is more significant for improving the accuracy of a seismic damage assessment than the quality of the sensors used; (2) the influence of population density can be considered using the proposed framework; and (3) the proposed framework can quantitatively consider the influence of sensor quality and spatial density on the rapid regional seismic damage assessment of buildings, which provides an important reference for the deployment of a strong-motion network for a given budget. Highlights: A cost-benefit analysis framework of sensor quality and spatial density for regional seismic damage assessment is proposed. The influence of sensor quality and spatial density on regional seismic damage assessment was quantitatively analyzed. The influence of population density can be considered using the proposed framework. The proposed method provides references for the deployment of sensors for a given budget considering the life-time cost.